Interferon Lambda: Opportunities, Risks, and Uncertainties in the Fight Against HCV - Laidlaw, Stephen M.; Dustin, Lynn B. (Frontiers in Immunology, 2014)
Innate immunity is key to the fight against the daily onslaught from viruses that our bodies are subjected to. Essential to this response are the interferons (IFNs) that prime our cells to block viral pathogens. Recent evidence suggests that the Type III (λ) IFNs are intimately associated with the immune response to hepatitis C virus (HCV) infection. Genome-wide association studies have identified polymorphisms within the IFN-λ gene locus that correlate with response to IFNα-based antiviral therapy and with spontaneous clearance of HCV infection. The mechanisms for these correlations are incompletely understood. Restricted expression of the IFN-λ receptor, and the ability of IFN-λ to induce IFN-stimulated genes in HCV-infected cells, suggest potential roles for IFN-λ in HCV therapy even in this era of directly acting antivirals. This review summarizes our current understanding of the IFN-λ family and the role of λ IFNs in the natural history of HCV infection.